Karakteristik hard candy minyak atsiri daun kemangi dengan penambahan ekstrak daun kelor (Moringa oleifera) - Nanda Ayu Hapsari; Bara Yudhistira; Rohula Utami (AGROINTEK, 2023)
Hard candy is one of the most favorite foods among Indonesian people. To increase the benefits and nutritional values of hard candy, basil essential oil and moringa leaf extract are added. Basil essential oil and moringa leaf extract contain various functional compounds, such as antioxidants that are beneficial for health. The purpose of characteristic basil essential oil hard candy with variation of moringa leaves extract addition, which is to find out physical, chemical, and sensory effect of adding moringa leaves extract, and knowing the best formula for hard candy. This study uses a completely randomized design (RAL) with one factor, concentration ratio between moringa leaves extract and water. The addition of moringa leaves extract and water in each sample is 80%:20%, 60%:40%, 50%:50%, 40%:60%, and 20%:80%, with three times repeating sample and two times repeating the analysis. The obtained data were analyzed by SPSS one way ANOVA then if there were real difference, further tests were performed with Duncan Multiple Range Test (DMRT) with significant rate 95%. The addition of moringa leaves extract affected hard candy’s physical characteristic hue color, chemical characteristic antioxidant activity, and sensory characteristic color, taste, and overall parameters. The best hard candy formula is hard candy F5(20% moringa extract : 80% water) with hue color 80,009 (yellow red), hardness 449,435 N, cohesiveness 0,010, water content 1,704%, ash content 2,194%, reduction sugar content 18,343%, water activity 0,525, pH 6,417, and antioxidant activity 20,910%